Hot spots of leprosy in the endemic area of São Luís, Maranhão State, Northeastern Brazil - Delma B. de Sousa; Reinaldo Souza-Santos; Mônica Duarte da Cunha; Andréa Sobral (Elsevier, 2020)
Background: Despite the decreasing of leprosy cases in Brazil, its occurrence remains high in certain Brazilian cities. The aim of the study was to analyze the spatial pattern of leprosy in São Luís, capital of Maranhão State, Northeastern Brazil. Methodology: An ecological study was carried out based on secondary data from leprosy cases and contacts reported in the Notification of Injury Information System in2015, and information on residency domiciles in three districts in the city. Results: A positive correlation was found between the leprosy cases and the average number of residents per household, and households with open sewage, garbage accumulated, with street identification, persons without income, dependents and the poor. A negative correlation between cases and households with a sidewalk, literate people and 60 years old or more were identified. The seropositivity of contacts examined using the ML Flow test was of 23.19%. The disease presents a heterogeneous spatial pattern, with hyperendemic clusters. Conclusions: The spatialization of both leprosy cases and contacts and the identification of areas presenting the highest concentration of the disease in each district is important and constitutes an important tool to subsidize disease-control actions. Keywords: Leprosy, Epidemiology, Spatial analysis